2023
DOI: 10.3390/min13060736
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Lanthanides(III) from Aqueous Nitric Acid Solutions with Tetra(n-octyl)diglycolamide into Methyltrioctylammonium Bis(trifluoromethanesulfonul)imide Ionic Liquid and Its Mixtures with Molecular Organic Diluents

Abstract: The extraction of lanthanides(III) from aqueous nitric acid solutions with tetra(n-octyl)diglycolamide into methyltrioctylammonium bis(trifluoromethanesulfonul)imide ([N1888][Tf2N]) ionic liquid and its mixtures with molecular organic diluents is investigated in this study. This study also investigates the effect of HNO3 concentration in the aqueous phase on the extraction of Ln(III) ions. Subsequently, the stoichiometry of the extracted complexes is determined, and the mechanism of Ln(III) extraction in a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…These series of references [54][55][56] investigated the extraction of lanthanides using the extractants showed in the next Table 9. Studying these references, it can be concluded that the data has not practical interest since the diluent used in the investigation is highly toxic, the same can be extended to the results derived from the utilization of nitrobenzene, chloroform and 1,2-dichloroethane using TODGA plus ILs in the extraction of the lanthanides.…”
Section: Ionic Liquid Acronysmmentioning
confidence: 99%
“…These series of references [54][55][56] investigated the extraction of lanthanides using the extractants showed in the next Table 9. Studying these references, it can be concluded that the data has not practical interest since the diluent used in the investigation is highly toxic, the same can be extended to the results derived from the utilization of nitrobenzene, chloroform and 1,2-dichloroethane using TODGA plus ILs in the extraction of the lanthanides.…”
Section: Ionic Liquid Acronysmmentioning
confidence: 99%
“…Turanov et al [205] explored the extraction of trivalent lanthanides from nitric acid aqueous solution. They investigated the extraction of Ln(III) ions (concentrations 0.002 mM) using TODGA(N,N,N,N Tetraoctyl Diglycolamide, C 36 H 72 N 2 O 3 ) and TBP (Tributyl phosphate, C 12 H 27 O 4 P) neutral extractants, along with [N1888][Tf 2 N] ionic liquid as a diluent.…”
Section: Cation Exchange Mechanism [Cat]mentioning
confidence: 99%